Implications of NÎµ-(Carboxymethy)lysine in altered metabolism of low density lipoproteins in patients with type 2 diabetes and coronary artery disease - Ahmed, K.A.A.; Muniandy, S.; Ismail, I.S. (2008)
The aim of this study is to evaluate the role of the glycoxidation product, NÎµ-(carboxymethyl)lysine (CML), on the metabolism of LDL which can give rise to increased risks of Coronary Artery Disease (CAD) in Type 2 Diabetes Mellitus (T2DM) patients. Polyclonal anti-CML antibodies, were used for measurement of serum CML. CML concentrations were measured by competitive enzyme-linked immunosorbent assay (ELISA) in the serum of 81 T2DM patients with CAD, 86 T2DM without CAD and 104 healthy subjects. LDLs from the study groups were isolated and labeled with the fluorescence dye, 1, 1â²-dioctadecyl-3, 3, 3â², 3â²-tetramethylindo carbocyanine perchlorate (DiI). LDL from healthy subjects was subjected to oxidation and glycation. Receptor-mediated uptake of labeled native and modified-LDL was studied in human hepatocellular carcinoma (HepG2) cells. CML concentrations were significantly higher in T2DM with CAD patients than diabetic patients but without CAD (529.5Â±83.6 vs. 425.1Â±64.4 ng mL-1, p<0.001). The uptake of DiI-LDL from type 2 diabetes patients without CAD was significantly lower than that for LDL from diabetic patients without CAD or glycated-LDL in HepG2 cells. This study demonstrated that CML may be largely responsible for the defective uptake of LDL of T2DM with CAD. Thus, CML may be used as endogenous biomarker for early detection of CAD in type 2 diabetes patients and may be considered as a new goal for the glycemic control in those patients.